2018
DOI: 10.3389/fnins.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

No Gender Differences in Egocentric and Allocentric Environmental Transformation After Compensating for Male Advantage by Manipulating Familiarity

Abstract: The present study has two-fold aims: to investigate whether gender differences persist even when more time is given to acquire spatial information; to assess the gender effect when the retrieval phase requires recalling the pathway from the same or a different reference perspective (egocentric or allocentric). Specifically, we analyse the performance of men and women while learning a path from a map or by observing an experimenter in a real environment. We then asked them to reproduce the learned path using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
5
27
1
Order By: Relevance
“…Accordingly, it is necessary to find an optimal level of difficulty [8]. Our results also confirm recent findings reporting that women are as accurate as men [63] provided that both groups are given a sufficient amount of time to learn spatial relationships and repetitions. Therefore, the degree of familiarity with the environment would play a role as a modulating factor, making up for men's advantage.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, it is necessary to find an optimal level of difficulty [8]. Our results also confirm recent findings reporting that women are as accurate as men [63] provided that both groups are given a sufficient amount of time to learn spatial relationships and repetitions. Therefore, the degree of familiarity with the environment would play a role as a modulating factor, making up for men's advantage.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, we observed that men spent more time learning the location of the objects. Although these results may seem to go against the previous literature (Piccardi et al, 2011b; Nori et al, 2018), we hypothesized that the fact that men took more time in the learning phase was not related to spatial orientation, but rather to their interest in the technology we used in this experiment. We observed that men were more enthusiastic about the AR app than women, paying more attention to how the AR app works and taking more time to observe the AR objects in detail, from a closer distance.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, it has been described that familiarity with the environment can influence participants’ performance in a real environmental spatial learning task, improving skills (Nori and Piccardi, 2011; Nori et al, 2018). In fact, familiarity with the environment allows more successful navigation in people with a poorer navigation style (Piccardi et al, 2011a), and the effect is more evident when, as in our experiment, participants move around freely in a real environment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the knowledge that the neurobiological process of memory consolidation extends well beyond the experimental time intervals, raising the possibility that tests using shorter delays (such as the WalCT) might not be fully sensitive to detecting subtle neurocognitive changes produced by OC use. In addition, the learning phase seems to be more sensitive to gender differences than the following retrieval phase, as also evidenced in other studies with other memory paradigms and longer delays (e.g., [ 21 , 22 , 57 , 58 ]). Putting this evidence together, we can speculate that learning is more sensitive to individual differences.…”
Section: Discussionsupporting
confidence: 72%